2017
DOI: 10.1080/09205063.2017.1331872
|View full text |Cite
|
Sign up to set email alerts
|

Cytocompatible polyion complex gel of poly(Pro-Hyp-Gly) for simultaneous rat bone marrow stromal cell encapsulation

Abstract: Polyion complex (PIC) gel of poly(Pro-Hyp-Gly) was successfully fabricated by simply mixing polyanion and polycation derivatives of poly(Pro-Hyp-Gly), a collagen-like polypeptide. The polyanion, succinylated poly(Pro-Hyp-Gly), and the polycation, arginylated poly(Pro-Hyp-Gly), contain carboxy (pK = 5.2) and guanidinium (pK = 12.4) groups, respectively. Mixing the polyanion and the polycation at physiological pH (pH = 7.4) resulted in PIC gel. The hydrogel formation was optimum at an equimolar ratio of carboxy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Collagen like polypeptides (CLPs), based on the natural collagen amino acid motifs, Gly-Pro-X and Gly-X-Hyp, adopt a poly(proline) II helix and then further associate into triple helical structures [9][10][11]. The CLPs have yielded materials in which cells can be easily encapsulated with high viability, proliferation, and desired morphology [12,13], characteristics that can be enhanced in hydrogels made with other polymers such as PEG when crosslinked with CLPs [14]. In addition, combining CLPs with other polypeptides imparts new functions to the CLPs, as it has been shown with self-healing upon crosslinking with silk-like polypeptides.…”
Section: Introductionmentioning
confidence: 99%
“…Collagen like polypeptides (CLPs), based on the natural collagen amino acid motifs, Gly-Pro-X and Gly-X-Hyp, adopt a poly(proline) II helix and then further associate into triple helical structures [9][10][11]. The CLPs have yielded materials in which cells can be easily encapsulated with high viability, proliferation, and desired morphology [12,13], characteristics that can be enhanced in hydrogels made with other polymers such as PEG when crosslinked with CLPs [14]. In addition, combining CLPs with other polypeptides imparts new functions to the CLPs, as it has been shown with self-healing upon crosslinking with silk-like polypeptides.…”
Section: Introductionmentioning
confidence: 99%
“…NS = not significant the succinylated-BC. It has been reported that succinylation of a collagen-like polypeptide similarly did not influence the biocompatibility of the polypeptide for rBMSCs [20][21]. Considering its biocompatibility, bioactivity and the ability of the cells to differentiate into bone cells, the succinylated-BC has potential as a 3D scaffold for reconstructing damaged bone.…”
Section: Biocompatibilitymentioning
confidence: 99%